2011
DOI: 10.1007/s11051-011-0544-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide and platinum nanoparticles protect cells from oxidant-mediated apoptosis

Abstract: Catalytic nanoparticles represent a potential clinical approach to replace or correct aberrant enzymatic activities in patients. Several diseases, including many blinding eye diseases, are promoted by excessive oxidant stress due to reactive oxygen species (ROS). Cerium oxide and platinum nanoparticles represent two potentially therapeutic nanoparticles that de-toxify ROS. In the present study we directly compare these two classes of catalytic nanoparticles. Cerium oxide and platinum nanoparticles were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 37 publications
4
60
0
1
Order By: Relevance
“…Similar data were delivered by Nomura et al, 8 showing that PtNPs inhibit RANKL-stimulated osteoclast differentiation via their ROS-scavenging property. Moreover, a study by Clark et al 22 showed that PtNPs reduce oxidantmediated apoptosis in target cells, judging by the activation of caspase 3. Nevertheless, there are also reports suggesting that PtNPs might have toxic effects on cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar data were delivered by Nomura et al, 8 showing that PtNPs inhibit RANKL-stimulated osteoclast differentiation via their ROS-scavenging property. Moreover, a study by Clark et al 22 showed that PtNPs reduce oxidantmediated apoptosis in target cells, judging by the activation of caspase 3. Nevertheless, there are also reports suggesting that PtNPs might have toxic effects on cells.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable effect was based on the radical scavenging and the UV light absorption property of CeO 2 nanoparticles. It is supposed that the aqueous sol is appropriate for some biochemical applications such as UV-screening cosmetics 25), 30) and enzymatic replacement therapy, 4) because the utilization of sol easily realizes a precise adjustment of administration concentration as compared with powder sample. In order to enhance the protecting effect of CeO 2 nanoparticles, morphology, and doping of different cations on the photo-induced DNA damage including fragmentation and deformation will be investigated in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that at an equal doses of 48 mg/mL, the CNPs were able to show higher in vitro SOD activity when compared to the PNPs which showed a lower SOD activity and also that the CNPs were more effective than platinum NPs in the protection of the human breast fibrosarcoma cells from cell death induced by the activities of hydrogen peroxide [90].…”
Section: Pnps Verses Cnpsmentioning
confidence: 98%